The Effect of Feeding Local and Imported Fish Meal on Daily Weight Gain, Sexual Performance, and Semen Production of Kacang Buck - Addulah, Marjuki; Kusmartono, Kusmartono; Suyadi, Suyadi; Soebarinoto, Soebarinoto; Winugroho, Mohammad (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2007)
This research was aimed to compare quality of local fish meal and imported ones, mainly in term of their effects on daily weight gain, feed efficiency, sexual performance, and semen production of Kacang goat bucks. Fifteen bucks were allotted to Randomized Block Design with three treatments and 5 replications. Treatment A was concentrate containing 14.10% soy bean meal and 0.90% urea, treatment B and C were concentrate containing 15% of local and imported fish meal, respectively. Each buck was put in individual cage, fed on elephant grass ad libitum and the concentrate of 1.50% body weight. Variables measured were daily weight gain, feed efficiency, sexual performance, and semen production. Semen was collected twice a week for 8 weeks. The results showed that feeding concentrate either containing local fish meal (treatment B) or imported fish meal (treatment C) gave no significantly different effect on daily weight gain, feed efficiency, sexual performance, and semen production. However both treatments gave better effect on the variables than those feeding concentrate containing soy bean meal and urea (treatment A). Based on these results, it could be concluded that quality of local fish meal was not significantly different from imported ones. Thus, it can be used to argue the perception of fish meal consumers that quality of local fish meal is lower than imported ones. (Animal Production 9(2): 135-144 (2007)Key Words: Fish meal, local, goat